Implementasi Green School berbasis Vertical Garden botol bekas di MTs Nurul Huda Babadan Ngajum - Husna, Nurul Aliefiatul; Subekti, Maulana Tri; Farhan, Dimasruhin; Isnaini, Lalu Muh; Rohmah, Nihlah Alifatul; Syahro, Fatimatus; Zahrani, Amalia Putri; Khoiriyah, Azrotul; Ahada, Nur; Agung, Yusuf Ratu (Maliki Interdisciplinary Journal, 2026)
This study aims to describe the implementation of a green school program through the use of discarded plastic bottles as vertical garden media at MTs Nurul Huda Babadan Ngajum and to examine its impact on the school’s physical environment. The research employed a descriptive qualitative approach supported by simple quantitative data. Qualitative data were collected through observation, interviews, and documentation to capture the implementation process and stakeholder involvement. Quantitative data included the number of plastic bottles utilized and the number of vertical garden units produced. The program was conducted in a participatory manner involving students and university students participating in a community service program as facilitators. Activities included collecting used bottles, preparing planting media, planting, and installing vertical garden units on school walls. Quantitative findings show that the program produced six vertical garden units using eighteen used plastic bottles. Qualitatively, the program improved the school environment by transforming previously empty walls into greener and more aesthetically pleasing spaces. The activity also increased student participation and supported contextual, environment-based learning. The findings indicate that school greening initiatives can be implemented in an economical, practical, and sustainable way through vertical space utilization and plastic recycling. This model has the potential to be replicated in other schools with limited land.